Evolutionary Rescue of an Environmental Pseudomonas otitidis in Response to Anthropogenic Perturbation - García-Ulloa, Manuel II; Escalante, Ana Elena; Moreno-Letelier, Alejandra; Eguiarte, Luis E.; Souza, Valeria (Frontiers in Microbiology, 2021)
Anthropogenic perturbations introduce novel selective pressures to natural environments, impacting the genomic variability of organisms and thus altering the evolutionary trajectory of populations. Water overexploitation for agricultural purposes and defective policies in Cuatro Cienegas, Coahuila, Mexico, have strongly impacted its water reservoir, pushing entire hydrological systems to the brink of extinction together with their native populations. Here, we studied the effects of continuous water overexploitation on an environmental aquatic lineage of Pseudomonas otitidis over a 13 year period which encompasses three desiccation events. By comparing the genomes of a population sample from 2003 (original state) and 2015 (perturbed state), we analyzed the demographic history and evolutionary response to perturbation of this lineage. Through coalescent simulations, we obtained a demographic model of contraction-expansion-contraction which points to the occurrence of an evolutionary rescue event. Loss of genomic and nucleotide variation alongside an increment in mean and variance of Tajima's D, characteristic of sudden population expansions, support this observation. In addition, a significant increase in recombination rate (R/θ) was observed, pointing to horizontal gene transfer playing a role in population recovery. Furthermore, the gain of phosphorylation, DNA recombination, small-molecule metabolism and transport and loss of biosynthetic and regulatory genes suggest a functional shift in response to the environmental perturbation. Despite subsequent sampling events in the studied site, no pseudomonad was found until the lagoon completely dried in 2017. We speculate about the causes of P. otitidis final decline or possible extinction. Overall our results are evidence of adaptive responses at the genomic level of bacterial populations in a heavily exploited aquifer.